DOI: 10.47749/t/unicamp.2017.986561
|View full text |Cite
|
Sign up to set email alerts
|

Unitag

Abstract: como parte dos requisitos exigidos para a obtenção do título de Doutora em Engenharia Elétrica, na área de Automação. ResumoEste trabalho apresenta uma solução que permite uma visão multidisciplinar da situação acadêmica do aluno, onde foi desenvolvida uma ferramenta alternativa para a coleta de respostas a audiência a ser utilizada em sala de aula, com a totalização, armazenamento e apresentação dos resultados. Desta forma, alunos podem avaliar o seu desempenho como também professores e gestores podem avaliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
0
0
Order By: Relevance
“…Reduced row spacing increased seed yield since more plants could be grown in the same area, offsetting any decline in individual yield components. This result agrees with the results of [19][20][21], who found that there was a significant increase in seed yield with an increase in the plant density of faba beans. Table 7.…”
Section: Weight Of 100 Seeds (Gm)supporting
confidence: 92%
“…Reduced row spacing increased seed yield since more plants could be grown in the same area, offsetting any decline in individual yield components. This result agrees with the results of [19][20][21], who found that there was a significant increase in seed yield with an increase in the plant density of faba beans. Table 7.…”
Section: Weight Of 100 Seeds (Gm)supporting
confidence: 92%
“…Observation is usually done by reviewing, monitoring, and examining an object until it gets valid data. According to Muhammad Ilyas Ismail in the book Learning Evaluation: Basic Concepts, Principles, Techniques, and Procedures, observation can be interpreted as one of the data collection techniques that is more specific than other techniques [16]. In general, observation aims to collect data that can be used to answer various problems that arise.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, drones, or unmanned aircraft vehicles or systems, or UAVs or UAS, were developed exclusively for military purposes. However, subsequently, they have become widely used in civil applications across a variety of fields, such as disaster management [1], the delivery of goods and information [2], search operations [3]; [4], surveillance [5], managing wildfires [6], relay for ad hoc networks [7]; [8] wind estimation [9], civil security [10], agricultural and remote sensing [11], traffic monitoring [12], healthcare and health-related services [13]; [14]; [15], and emergency medical services [16].…”
Section: Introductionmentioning
confidence: 99%